2016
DOI: 10.1590/0101-60830000000072
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of burnout syndrome in medical students

Abstract: Background: Burnout syndrome (BS) is a set of psychological symptoms resulting from the interaction between chronic occupational stress and individual factors. These symptoms include emotional exhaustion, depersonalization and decreased professional satisfaction. BS is manifested in a variety of professions and is prevalent in contexts in which health professionals are required to interact directly with the public. Objective: To determine the prevalence of BS among medical students at a university in Ceará Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
3
36

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 21 publications
6
74
3
36
Order By: Relevance
“…[20][21][22][23][24][25] However, the majority of the Thai undergraduate medical students perceived either low personal accomplishment, high emotional exhaustion or depersonalisation, which is similar to studies conducted internationally. [20][21][22][23][24] This study suggests that students of male gender and lower academic performance were at higher risk of burnout. Although Backović and colleagues 25 found that female students were more vulnerable to stress and burnout, Chunming and colleagues 26 also indicated that male students had greater burnout risk.…”
Section: Associated Factorsmentioning
confidence: 58%
“…[20][21][22][23][24][25] However, the majority of the Thai undergraduate medical students perceived either low personal accomplishment, high emotional exhaustion or depersonalisation, which is similar to studies conducted internationally. [20][21][22][23][24] This study suggests that students of male gender and lower academic performance were at higher risk of burnout. Although Backović and colleagues 25 found that female students were more vulnerable to stress and burnout, Chunming and colleagues 26 also indicated that male students had greater burnout risk.…”
Section: Associated Factorsmentioning
confidence: 58%
“…30 Regarding the first year of medical school, Santen et al reported a burnout prevalence of 21% 31 and Almeida et al reported a prevalence of 14.9%. 32 Additionally, according to other studies, burnout increases across curricular years.…”
Section: Discussionmentioning
confidence: 86%
“…Studies capture varying degrees of perceived levels of stress suffered by medical students at Arab colleges, and its effects on their academic performance, such as Sudan, (50%), Egypt (60%), and Saudi Arabia, ranging from 53%-72% respectively (Dafaalla, 2016;Abdelrahman et al, 2013;Abdelghani et al, 2011;Paro et al, 2014). On the other hand, the prevalence of burnout syndrome is reportedly 10% to 45%, depending on the instrument used for diagnosis (Galan et al, 2014;Youssef, 2016;Ishak et al, 2013;Almeida, 2016;Chigerwe, 2014;Fawzy, 2017). Although low levels of exposure to stress can positively benefit students' performance and improve their academic dynamic (Heinen, 2017;Ludwig et al, 2015), yet it can have unfavourable effects on student outcomes when an imbalance occurs from such pressures, responsibilities and demands ( Ibrahim et al, 2013;Cecil, 2014;Muzafar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Stress and burnout are endemic in multi-medical institutions and are usually exhibited early during the preclinical stage, ranging from 62-75%; whereas stress and burnout during the clinical stage range from 25.6-78% and 10-45%, depending on the instrument used for diagnosis (Galan et al, 2014;Youssef, 2016;Ishak et al, 2013). Regardless, only a few medical schools have already implemented mental well-being programs to support students during their clinical training periods, allowing them to graduate as healthy young physicians (Galan et al, 2014;Youssef, 2016;Ishak et al, 2013;Almeida, 2016;Chigerwe, 2014;Fawzy, 2017;Sohail, 2013).…”
Section: Introductionmentioning
confidence: 99%